Organization of heart failure management in European Society of Cardiology member countries: survey of the Heart Failure Association of the European Society of Cardiology in collaboration with the Heart Failure National Societies/Working Groups. (September 2013) - Seferović, Petar M.; Stoerk, Stefan; Filippatos, Gerasimos; Mareev, Viacheslav; Kavoliuniene, Ausra; Ristić, Arsen D.; Ponikowski, Piotr; McMurray, John; Maggioni, Aldo; Ruschitzka, Frank; van, Dirk J.; Coats, Andrew; et al.
<x xml:space="preserve">Abstract</x> Aims The aim of this document was to obtain a real‐life contemporary analysis of the demographics and heart failure (HF) statistics, as well as the organization and major activities of the Heart Failure National Societies (HFNS) in European Society of Cardiology (ESC) member countries. Methods and results Data from 33 countries were collected from HFNS presidents/representatives during the first Heart Failure Association HFNS Summit (Belgrade, Serbia, 29 October 2011). Data on incidence and/or prevalence of HF were available for 22 countries, and the prevalence of HF ranged between 1% and 3%. In five European and one non‐European ESC country, heart transplantation was reported as not available. Natriuretic peptides and echocardiography are routinely applied in the management of acute HF in the median of 80% and 90% of centres, respectively. Eastern European and Mediterranean countries have lower availability of natriuretic peptide testing for acute HF patients, compared with other European countries. Almost all countries have organizations dealing specifically with HF. HFNS societies for HF patients exist in only 12, while in 16 countries HF patient education programmes are active. Most HFNS reported that no national HF registry exists in their country. Fifteen HFNS produced national HF guidelines, while 19 have translated the ESC HF guidelines. Most HFNS (n = 23) participated in the organization of the European HF Awareness Day. Conclusion This document demonstrated significant heterogeneity in the organization of HF management, and activities of the national HF working groups/associations. High availability of natriuretic peptide and echocardiographic measurements was revealed, with differences between developed countries and countries in transition.